2021
DOI: 10.3389/fncel.2020.620020
|View full text |Cite
|
Sign up to set email alerts
|

HMGA1 Induction of miR-103/107 Forms a Negative Feedback Loop to Regulate Autophagy in MPTP Model of Parkinson’s Disease

Abstract: Autophagy dysfunction has been directly linked with the onset and progression of Parkinson’s disease (PD), but the underlying mechanisms are not well understood. High-mobility group A1 (HMGA1), well-known chromatin remodeling proteins, play pivotal roles in diverse biological processes and diseases. Their function in neural cell death in PD, however, have not yet been fully elucidated. Here, we report that HMGA1 is highly induced during dopaminergic cell death in vitro and mice models of PD in vivo. Functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 56 publications
2
8
0
Order By: Relevance
“…The acute mouse model of PD has been created by injecting MPTP four times within 6 h ( 55 , 56 ). The subacute mouse PD model has been produced by injecting MPTP once a day for several days to several weeks ( 57 ). Finally, the chronic mouse model has been created by injecting MPTP and probenecid at 3.5-day intervals for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The acute mouse model of PD has been created by injecting MPTP four times within 6 h ( 55 , 56 ). The subacute mouse PD model has been produced by injecting MPTP once a day for several days to several weeks ( 57 ). Finally, the chronic mouse model has been created by injecting MPTP and probenecid at 3.5-day intervals for 6 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that miR-103/107 forms a negative feedback loop with HMGA1 to regulate MPP + /MPTP-induced autophagy impairment and neural cell death (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…8g). Among these miRs, several (miR-93-5p, miR-107, and miR-486-5p) were reported to regulate apoptosis and cellular autophagy [26,28] and some (miR-24-3p, miR-132-3p, and miR-20a-5p) were reported to regulate inflammation response [14,43]. Collectively, these data show that EVs miRs contents are exacerbated with age and SCI, which are associated with neuroinflammation and disrupted autophagy-lysosome pathways-consistent with our NanoString results and indicating age-related dysregulation in these pathways after injury.…”
Section: Old Age Alters Evs Mirs Content Associated With Inflammation...mentioning
confidence: 99%